2020
DOI: 10.1186/s12866-020-01747-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the gut microbial community of rhesus macaques in high-altitude environments

Abstract: Background: The mammal intestinal microbiota is involved in various physiological processes and plays a key role in host environment adaption. However, for non-human primates (NHPs), little is known about their gut microbial community in high-altitude environments and even less about their adaption to such habitats. We characterised the gut microbial community of rhesus macaques from multiple high-altitude environments and compared it to those of low-altitude populations. Results: We collected faecal samples o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 80 publications
4
44
0
Order By: Relevance
“…In addition, the increase in diversity of human gut microbes also reflects better health and stronger metabolic capacity [ 17 ]. In this study, rumen microbial diversity of yaks increased with altitude, and was comparable to the gastrointestinal tract (GIT) microbial diversity of other mammals, such as pikas [ 11 ] and rhesus macaques [ 18 ]. Therefore, we speculate that the rumen communities of high-altitude yaks may have a higher ability to use high-fiber herbage to help them meet their energy needs in cold and high-altitude habitats.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In addition, the increase in diversity of human gut microbes also reflects better health and stronger metabolic capacity [ 17 ]. In this study, rumen microbial diversity of yaks increased with altitude, and was comparable to the gastrointestinal tract (GIT) microbial diversity of other mammals, such as pikas [ 11 ] and rhesus macaques [ 18 ]. Therefore, we speculate that the rumen communities of high-altitude yaks may have a higher ability to use high-fiber herbage to help them meet their energy needs in cold and high-altitude habitats.…”
Section: Discussionmentioning
confidence: 69%
“…In addition to the observed potential probiotics, we found that a potentially pathogenic bacteria, Treponema , also increased with elevation. Some species of Treponema have been detected in the genital and oral tracts of humans [ 40 ], the rumen of yaks [ 41 ], and the gut of rhesus macaques [ 18 ]. They can cause various diseases in these organisms, such as syphilis, yaws, and papillomatous digital dermatitis [ 18 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCFA levels in Yak rumens are higher than those in cattle, thus helping them adapt to high altitudes ( Zhang et al, 2016 ). Other animals, such as black-necked cranes ( Grus nigricollis ) ( Wang et al, 2020 ), lizards ( Phrynocephalus vlangalii ) ( Zhang W. et al, 2018 ), Chinese Rhesus macaques ( Macaca mulatta ) ( Zhao et al, 2018 ; Wu et al, 2020b ), Bufo gargarizans ( Xu et al, 2020 ), Tibetan chickens ( Zhou et al, 2016 ) and Tibetan pigs ( Zeng et al, 2020 ), also have high abundances of Ruminococcus in their guts ( Table 1 ). These data indicate the importance of Ruminococcus in plateau adaptation and hypoxia-tolerant animals.…”
Section: Altitude-associated Hypoxia and The Gut Microbiotamentioning
confidence: 99%
“…Altitude also induces significant differences in their bacterial communities' structure (Lan et al, 2017). The effects of altitude on bacterial alpha diversity and communities' structure has been confirmed in animal experiments (Wu et al, 2020). A skin microbiota study found that human skin microbiota's beta diversity increases with altitude (Li et al, 2019b).…”
Section: Differences In the Diversity Of Intestinal Microbiota Between Han And Tibetan Womenmentioning
confidence: 87%